THE RATIONALE FOR THE DEVELOPMENT OF RECOMMENDATIONS ON THE SELECTION OF MODES OF GRINDING OF THE RESTORED CRANKSHAFTS - V. V. Elistratov; A. V. Agoshkov; E. V. Evdokymov; V. V. Makarenko (Вестник СибАДИ, 2017)
In this article is described the shortcomings of existing methods of recovery of necks of the crankshafts. Crankshafts restore to the nominal size, grind on grinding machine, and install on engine after overhauling. The main problem of this process is low resource of crankshafts after repair. This article proves the necessity of developing of recommendations on the selection of modes of grinding of the restored crankshafts. When today, the processing of the restored crankshafts no difference from processing of a new product.